2003
DOI: 10.1038/sj.npp.1300200
|View full text |Cite
|
Sign up to set email alerts
|

Acute Influences of Estrogen and Testosterone on Divergent and Convergent Thinking in Postmenopausal Women

Abstract: Previous studies indicated an enhanced capability of divergent creative thinking in young women during the ovulatory phase, which expressed itself also by an increased dimensional complexity of ongoing electroencephalographic (EEG) activity. Considering the enhanced plasma levels of estrogen and testosterone characterizing the ovulatory phase, we tested whether short-term administration of estrogen or testosterone in postmenopausal women with constantly low levels of gonadal steroids induces similar changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Several recent studies observed rather rapid effect of estradiol on some aspects of cognitions, with the earliest changes being reported after 3 days of treatment (e.g. Duka et al 2000;Krug et al 2003). Since in the present study the first treatment effects were assessed after 4 weeks, the possibility that some temporary favourable effects had already disappeared again can not be ruled out.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Several recent studies observed rather rapid effect of estradiol on some aspects of cognitions, with the earliest changes being reported after 3 days of treatment (e.g. Duka et al 2000;Krug et al 2003). Since in the present study the first treatment effects were assessed after 4 weeks, the possibility that some temporary favourable effects had already disappeared again can not be ruled out.…”
Section: Discussionmentioning
confidence: 57%
“…Subjects in those studies were either symptomatic women, suffering from menopausal insomnia (Anderer et al 2003) or depression (Saletu et al 1995(Saletu et al , 2002 or younger women (mean age 58 years), when compared to subjects in the present study (Krug et al 2003). In addition, two observational studies reported that brainstem potentials were modified by gonadal hormones in asymptomatic postmenopausal women aged 47-55 years (Caruso et al 2000(Caruso et al , 2003.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A cross-over study of only 3 days compared transdermal T vs. placebo (n=12) and transdermal E2 vs. placebo (n=12) in postmenopausal women reported that E2 impaired divergent thinking and improved convergent thinking, motor preservation and verbal memory. T's effect were opposite to that of E2 in that it improved performance on some divergent thinking tasks [90].…”
Section: Testosterone Replacement Therapy and Cognition In Womenmentioning
confidence: 76%
“…This was interpreted as a loss of control over perseveration, which corresponds to the more recent concepts of flexibility and inhibitory control (Miyake et al, 2000). A number of researchers have used the original (not yet computerized) MPT to study psychiatric and neurological disorders, such as schizophrenia (Axmacher, Bente, & Ferner, 1970;Mittenecker, 1953Mittenecker, , 1960Morrens, Hulstijn, Lewi, De Hert, & Sabbe, 2006;Morrens, Hulstijn, Lewi, & Sabbe, 2008;, Parkinson's disease (Stoffers et al, 2001;Stoffers et al, 2007), and epilepsy (Remschmidt, 1970(Remschmidt, , 1973Ruser, 1990), as well as individual differences and intraindividual variations in healthy samples (Krug, Mölle, Dodt, Fehm, & Born, 2003;Krug, Stamm, Pietrowsky, Fehm, & Born, 1994;Perras, Smolnik, Fehm, & Born, 2001;Schulter, 1987). Together, the findings confirmed that higher context redundancy was related to restricted cognitive flexibility.…”
Section: Execution Of the Testmentioning
confidence: 99%